Fibre-reinforced multifunctional SiC matrix composite materials. (3rd April 2017) - Yin, X. W.; Cheng, L. F.; Zhang, L. T.; Travitzky, N.; Greil, P.
Abstract : In the last two decades, fibre-reinforced SiC ceramic-matrix composites (CMCs) have attracted extensive interests. Owing to the designable multi-scale microstructure feature and the tailorable processing methods such as chemical vapour infiltration and polymer derived ceramics, SiC matrix composites attain great potential as multifunctional composites. Through designing the fibre, interphase, matrix and coating, the composite exhibits a multitude of functionalities which are desirable for various technological applications. Besides strengthening and toughening design of CMCs, three inspiring issues of multifunctional CMCs are receiving increasing attention, including crack self-healing, friction self-lubrication, and electromagnetic shielding and absorption, which are the key mechanisms to promote the application of CMCs in hot structures of engines and aerospace vehicles, braking pads/discs, various electronic devices, etc. The present review covers the main mechanisms on strengthening and toughening, crack self-healing, friction self-lubrication, and electromagnetic shielding and absorption of CMCs. Key developments and future challenges in this field are summarised.